PENDEKATAN FRUGAL INNOVATION PADA KOMUNITAS PEMILIK BISNIS PROPERTI DI INDONESIA: STUDI KASUS HOTEL BUDGET DAN RUMAH KOS - Renita Kawuryan, MBA; Christie Stephanie Piar, S.IP., M.M (Prosiding Seminar Nasional Terapan Riset Inovatif (SENTRINOV), 2024)
The advancement of information technology has led to significant transformations in the human way of life. WhatsApp is a widely utilized mobile application boasting a substantial user base of over 2.7 billion people. Utilizing WhatsApp groups within business communities as a platform for facilitating information exchange. In developing nations, the majority of the population favors products and services that are adaptable, affordable, and easily accessible. Frugal innovation is about creating cost-effective solutions that cater to the financial constraints of these communities. Business individuals with little financial resources frequently depend on more basic technologies. This study applied the Netnography methodology to investigate the business practices and interpersonal interactions within the WhatsApp group of the Property Business Owner Community. The dataset collected over the period from July 31st, 2022 to September 14th, 2023 has a total of 40,199 messages contributed by 428 individuals within the group. The analysis of frugal innovation’s findings reveals a number of business innovations such as consultation services addressing issues related to boarding houses, utilization of property advertising media, access to reliable banking data for loan purposes in Indonesia, provision of legal assistance, choose the best product for the business and information regarding blacklist consumer.